The role of entrepreneurship in stimulating economic growth in developed and developing countries - Justin Doran; Nóirín McCarthy; Marie O'Connor (Cogent Economics & Finance, 2018)
This paper analyses whether different measure of entrepreneurship can explain economic growth. It utilises 14 difference indicators of entrepreneurship to analyse the contribution of entrepreneurial activity, aspirations, and attitudes to Gross Domestic Product (GDP) per capita. It also examines whether the importance of entrepreneurship varies across high-income and middle/low-income countries. An unbalanced panel of 55 countries over the time period 2004-2011 is used. Fourteen different indicators of entrepreneurship are utilised and are condensed into three components using principle components analysis. Regression analysis is then used to assess whether these three different components of entrepreneurship drive economic growth. The results indicate that entrepreneurial attitudes are found to stimulate GDP per capita in high-income countries while entrepreneurial activity is found to have a negative effect in middle/low-income
Keywords: 330; Entrepreneurship; economic growth; developing countries